Suitability and Potential Nutrient Contribution of Underutilized Foods in Community-Based Infant Foods in Northern Ghana - Kubuga, C.K.; Bantiu, C.; Low, Jan W. (MDPI, 2023)
In rural Ghana, infant feeding is largely home-based or community-based yet less is known about the kinds of community-based infant foods and the ability of families to create a range of recipes for baby feeding using context-specific ingredients particularly in northern Ghana which has a high prevalence of malnutrition. In this explorative study on mothers (15–49 years; n = 46), we investigated community-based infant foods’ food group composition, enrichment, nutrient contribution, and acceptability. The identified community-based infant foods were mainly made of either corn or millet porridges in northern Ghana and had three nutrients with % RNI ≥ 70. We developed 38 recipes of enriched community-based infant foods adding underutilized foods (orange-fleshed sweet potato, pawpaw, cowpea, moringa, groundnut, Bambara beans, and soya beans) to increase the number of nutrients from three to at least five and at most nine nutrients with % RNI ≥ 70 based on the recipe combinations. The enriched community-based infant food recipes provided adequate caloric amounts and modest improvements in micronutrient content for infants (6–12 months). All recipes tested were deemed appropriate and acceptable for infants by mothers. Moringa and pawpaw emerged as the lowest-cost ingredients to add among the underutilized foods. Future research is necessary to assess the effectiveness of the new recipes at promoting linear growth and improving micronutrient status during the complementary feeding period.